Managing Home Infusion Therapy. Issue 12 (December 2020) - Fields, Bronwyn E.; Whitney, Robin L.; Bell, Janice F.
Abstract : This article is part of a series, Supporting Family Caregivers: No Longer Home Alone, published in collaboration with the AARP Public Policy Institute. Results of focus groups, conducted as part of the AARP Public Policy Institute's No Longer Home Alone video project, supported evidence that family caregivers aren't given the information they need to manage the complex care regimens of family members. This series of articles and accompanying videos aims to help nurses provide caregivers with the tools they need to manage their family member's health care at home. Nurses should read the articles first, so they understand how best to help family caregivers. Then they can refer caregivers to the informational tear sheet— Information for Family Caregivers —and instructional videos, encouraging them to ask questions. For additional information, see Resources for Nurses . Abstract : This article—one in a series published in collaboration with the AARP Public Policy Institute—presents instructions and tips nurses can use to educate and support caregivers of people receiving home infusion therapy.